Studi Deskriptif tentang Persepsi Mahasiswa terkait dengan Inovasi yang dapat Dilakukan Penyelenggara Pendidikan Tinggi - Andrew, Richard; Claudia, Michelle (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2022)
Nowadays, higher education administrators faced high global challenges and this situation similar with the other business and social sectors. All of those administrators must prepare solutions and innovations to sustain in post-normalization era. This research objective is to find the urgency of innovation as general for higher education academic and non-academic environments. The research used descriptive analysis method and took 145 samples from Universitas Tarumanagara students. There are plenty of innovation in this research such as marketing, digital infrastructure, learning process, curriculum, student organization, education administration and education facilities. Overall, research findings explain the big benefit of education innovation for the sustainable development of higher educations.